Pengaruh Debt To Equity Ratio, Current Ratio, Size, dan Cash Flow terhadap Kinerja Perusahaan yang Dimoderasi Kebijakan Dividen pada Industri Manufaktur (Sub Sektor Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Roma, Heribetus Boli; Rinofah, Risal; Sari, Pristin Prima (Universitas Batanghari Jambi, 2024)
This research aims to analyze the influence of debt to equity ratio (DeR), current ratio (CR), firm size and cash flow on company performance and dividend policy as moderation. This type of research is quantitative descriptive. The research sample was 18 manufacturing companies in the food and beverage sub-sector. The research method used is multiple linear regression analysis. The research results show that debt to equity ratio (DeR), company size (firm size) and cash flow have a positive and significant effect on company performance, but the current ratio (CR) has no effect on company performance in the manufacturing industry sub-sector of food and beverage companies which is listed on the Indonesian Stock Exchange. Furthermore, this research also found that dividend policy was able to moderate the debt to equity ratio (DeR), company size (firm size) and cash flow variables on company performance, but the dividend policy variable was not able to moderate the current ratio (CR) on performance. companies in the food and beverage company sub-sector manufacturing industry listed on the Indonesia Stock Exchange for the 2017-2021 period.